Ebola Patient Virus Cycle Threshold and Risk of Household Transmission of Ebola Virus. (19th December 2019) - Reichler, Mary R; Bruden, Dana; Thomas, Harold; Erickson, Bobbie Rae; Knust, Barbara; Duffy, Nadia; Klena, John; Hennessy, Thomas; ,
Abstract: Background: Identifying risk factors for household transmission of Ebola virus (EBOV) is important to guide preventive measures during Ebola outbreaks. Methods: We enrolled all confirmed persons with EBOV disease who were the first case patient in a household from December 2014 to April 2015 in Freetown, Sierra Leone, and their household contacts. Index patients and contacts were interviewed, and contacts were followed up for 21 days to identify secondary cases. Epidemiologic data were linked to EBOV real-time reverse-transcription polymerase chain reaction cycle threshold (Ct) data from initial diagnostic specimens obtained from enrolled index case patients. Results: Ct data were available for 106 (71%) of 150 enrolled index patients. Of the Ct results, 85 (80%) were from blood specimens from live patients and 21 (20%) from oral swab specimens from deceased patients. The median Ct values for blood and swab specimens were 21.0 and 24.0, respectively ( P = .007). In multivariable analysis, a Ct value from blood specimens in the lowest quintile was an independent predictor of both increased risk of household transmission ( P = .009) and higher secondary attack rate among household contacts ( P = .03), after adjustment for epidemiologic factors. Conclusions: Our findings suggest the potential to use Ct values from acute EBOV diagnostic specimens for index patients as an early predictor of high-risk households and high-risk groups of contacts to help prioritize EBOV disease investigation and control efforts. Abstract : In a Sierra Leone study during the 2014–2015 Ebola outbreak, low cycle threshold values for the initial diagnostic specimens from index patients independently predicted an increased risk of household transmission and higher secondary attack rate among household contacts, after adjustment for epidemiologic factors.